Leukocyte Surface Biomarkers Implicate Deficits of Innate Immunity in Late‐onset Alzheimer's Disease. (20th December 2022) - Li, Yihan; Huang, Xin; Fowler, Christopher; Doecke, James D; Trounson, Brett; Pertile, Kelly; Rumble, Rebecca; Lim, Yen Ying; Maruff, Paul; Mintzer, Jacobo E.; Dore, Vincent; Rowe, Christopher; et al.
Abstract: Background: Alzheimer's disease (AD) is characterized by amyloid‐β (Aβ) plaques, neurofibrillary tangles, reactive astrogliosis, and microgliosis. Aberrant Aβ accumulation starts 20–30 years before clinical onset, so biomarker test is essential to diagnose people living with early AD. PET imaging and CSF measurements allow the diagnosis of preclinical and prodromal AD in research and clinical trials, but their invasiveness and costliness might limit their application in hospital setting. Therefore, developing non‐invasive population screening tests is necessary for the early diagnosis of AD. Recent genetic findings strongly implicate the role of innate and adaptive immunity in AD and suggest that a systemic failure of cell‐mediated Aβ clearance contributes to AD onset and progression. Our research question was to develop an immune‐related blood‐based biomarker test to facilitate the diagnosis and prognosis of AD. It was hypothesized that the pattern of immune‐related receptors and molecules expressed on peripheral leukocytes could differentiate people living with AD from healthy population. Method: We recruited 180 and 200 participants from AIBL in two discovery phases and validated our findings by an independent cohort of 112 participants from AIBL. A total of 34 innate and adaptive immunity‐related leukocyte antigens on peripheral lymphocytes, monocytes, and neutrophils were examined by flow cytometry immunophenotyping. Data was analysed by logistic regression and ROC analyses. Result: We identified upregulated CD35, CD59, CD91, RAGE, and Scara‐1 expressions and downregulated CD11c, CD18, CD36, CD163, MerTK, and P2X7 expressions on leukocytes of MCI/AD patients. Significant correlation between them and Aβ burden, episodic memory, and PACC score was observed, such as CD59 and CD91. Pathway analysis revealed upregulation of complement inhibition and downregulation of cargo receptor activity and Aβ clearance in AD. We proposed a marker panel including CD11c, CD59, CD91 and CD163 and this panel predicted patients' PET Aβ status with AUC of 0.93 (0.88 to 0.97), which was repeated in validation cohort. Regarding adaptive immunity, we did not see significant results. Conclusion: Our study suggested deficits in innate immunity in AD, which is consistent with genomic studies. Our proposed leukocyte‐based biomarker panel might be sensitive and practical for AD screening and diagnosis.